Islamic Perspective Gender Concept and Its Relevance to Social Resilience - Ahlan, Ahlan; Nurwahidah Nurwahidah; Rahman, Rahman; Lailiyatun Nafisah (STKIP Taman Siswa Bima, 2024)
Gender issues are currently still a serious discussion among academics. Even though it has been discussed for a long time, gender issues are still a polemic in society, this is because gender issues are very closely related to the movement for equality of roles and functions between men and women in all fields. The pros and cons of gender issues are commonplace because there are different points of view and open-mindedness in every society. It is certain that gender relations are very necessary to pay attention to in order to maintain social stability. Men and women basically have the same role in maintaining and maintaining, as well as enhancing a more constructive social system. This paper uses a qualitative approach, using the library research method. The data in this paper were obtained from various literal sources, both books, journals, and scientific articles related to the study of gender and social security. The results of this study show; 1) Gender in the Islamic perspective sees equality before God. Both have an important role in carrying out the mandate as servants of God. 2) Gender in the development of society has a role in both the private and publik spheres, such as in economic and political resilience.